Consequences of Traumatic Brain Injury for Human Vergence Dynamics - Tyler, Christopher W.; Likova, Lora T.; Mineff, Kristyo N.; Elsaid, Anas M.; Nicholas, Spero C. (Frontiers in Neurology, 2015)
Purpose: Traumatic brain injury involving loss of consciousness has focal effects in the human brainstem, suggesting that it may have particular consequences for eye movement control. This hypothesis was investigated by measurements of vergence eye movement parameters. Methods: Disparity vergence eye movements were measured for a population of 123 normally sighted individuals, 26 of whom had suffered diffuse traumatic brain injury (dTBI) in the past, while the remainder served as controls. Vergence tracking responses were measured to sinusoidal disparity modulation of a random-dot field. Disparity vergence step responses were characterized in terms of their dynamic parameters separately for the convergence and divergence directions. Results: The control group showed notable differences between convergence and divergence dynamics. The dTBI group showed significantly abnormal vergence behavior on many of the dynamic parameters. Conclusion: The results support the hypothesis that occult injury to the oculomotor control system is a common residual outcome of dTBI.